(untitled) (CAHIERS MAGELLANES-NS, 2024)
Let G be a (p, q) graph. Let f : V (G) ® 1, 2, 3,…,k be a function where kÎN and k>1. For each edge uv, assign the label f (uv) = . f is called k-Total geometric mean cordial labeling of G if | tmf (i) – tmf (j) | ≤ 1, for all i, jÎ1, 2, 3,…,k, where tmf (x) denotes the total number of vertices and edges labeled with x, xÎ1, 2, 3,…,k. A graph that admits the k-total geometric mean cordial labeling is called k-total geometric mean cordial graph. In this paper we investigate 4- total geometric mean cordial (4-TGMC) labeling behavior of some Tree related graphs.